Singapore : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Financial System Stability Assessment paper on Singapore highlights the attractiveness of Singapore as a financial center is underpinned by strong economic fundamentals, sound economic policies, and a sophisticated financial oversight framework. The financial system is exposed to global and regional macrofinancial shocks through significant trade and financial channels but appears resilient even under adverse scenarios. However, banks' US dollar liquidity is vulnerable to stress conditions. Fintech developments so far have focused on partnerships with existing financial institutions and do not appear to contribute significantly to systemic risk. Singapore authorities should continue to enhance its strong oversight of the financial system. Strengthening the framework for resolution and safety nets, namely by devoting more resources to the Monetary Authority of Singapore (MAS)' Resolution Unit; and enhancing the oversight of MAS Electronic Payments System by ensuring more staffing resources are two other important areas for action.